The Organization of the Hajj and the State: Cohesion and Rivalries within the Muslim Community of Côte d'Ivoire (1993-2006) - (:unkn) unknown (My University, 2016)
The importance of the hajj for Muslims and the considerable sums of money devoted to it arouse the envy of both religious and political actors. Thus, it is not surprising that since independence many West African states have often played a central role in the organization of the Muslim pilgrimage. In this regard, the case of Côte d'Ivoire is very interesting since the state recognized the Association Musulmane pour l'Organisation du Pèlerinage as the first official pilgrimage organizing association of the country in 1978. The aim of this communication is twofold. On the one hand, it shows how the planning of the hajj has been a vector of unity for Ivorian Islam. At the same time, it has fostered intense rivalries between several associations and Muslim leaders struggling for economic, religious and symbolic resources. On the other hand, the supposedly secular state has played a murky role in this business. The different Ivoirian political regimes from 1993 to 2006 have alternated between a policy of engagement and withdrawal. These strategies have allowed the ruling party to use patronage as an instrument to ensure the loyalty of some Muslim elites and to reduce the influence of other organizations and leaders suspected of being close to the opposition.
Keywords: African Research